2017
DOI: 10.3389/fneur.2017.00571
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Gamma Synchrony after Mild Traumatic Brain Injury and Its Correlation with White Matter Abnormality

Abstract: Mild traumatic brain injury (mTBI) has been firmly associated with disrupted white matter integrity due to induced white matter damage and degeneration. However, comparatively less is known about the changes of the intrinsic functional connectivity mediated via neural synchronization in the brain after mTBI. Moreover, despite the presumed link between structural and functional connectivity, no existing studies in mTBI have demonstrated clear association between the structural abnormality of white matter axons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 74 publications
0
17
1
Order By: Relevance
“…Of course, this statement only applies to the sensor constellation as used in this study, and not, for example, to data from IMUs positioned at the low back. Although methods derived from low back- or foot-mounted IMUs [ 12 , 13 , 20 , 47 ] may be less susceptible to turns, literature suggested that GE detection is easier and more robust from shank-mounted IMUs. [ 17 – 19 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, this statement only applies to the sensor constellation as used in this study, and not, for example, to data from IMUs positioned at the low back. Although methods derived from low back- or foot-mounted IMUs [ 12 , 13 , 20 , 47 ] may be less susceptible to turns, literature suggested that GE detection is easier and more robust from shank-mounted IMUs. [ 17 – 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…For both events we evaluated the detection performance in terms of correctly identified events (true positives, TP ), falsely identified events (false positives, FP ) and missed events (false negatives, FN ). TP s were defined as < 300 ms difference (in terms of magnitude) between an event detected by the IMU-based algorithm and the reference event [ 12 ]. From these metrics the recall, precision and F1 score were derived: Recall expressed how many of the gait events were detected and precision expressed how many of the detected gait events were true gait events.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, learning and memory largely depend on coherence, which enables long-distance communication between brain regions (Dü Zel et al, 2010;Wang et al, 2010). Several human imaging studies demonstrate that TBI disrupts synchronization (Sharp et al, 2011;Venkatesan et al, 2015;Wang et al, 2017), leading to the likely increase or decrease in functional network connectivity that contributes to long-term cognitive effects.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, memory processing is mainly contingent upon coherence, which allows long-distance interaction between various brain regions 38,39 . Recent findings in human imaging studies identified that TBI disturbs synchronization [40][41][42] , leading to the probable increase or decrease in functional network connectivity that contributes to long-term cognitive defects.…”
Section: Introductionmentioning
confidence: 99%